Korelasi Antara Adiksi Game Online dengan Perilaku Empati pada Remaja di Kabupaten Semarang - Mukti Ali; Farikha Nazilatus Salamah (Fakulatas Dakwah IAIN Salatiga, 2021)
The phenomenon of playing online games among teenagers is something that must be considered. Addiction to online games makes individuals do not care about interactions with people around them. Because individuals who have been addicted to online games are only focused on online games. As a result, the individual's feelings of empathy are not formed. The quantitative research method of correlation with online game addiction scale and empathy scale contains statements that are favorable and unfavorable. The sample in this study was 73 teenagers from Kalisari Hamlet. The results of the study showed that there was a moderate relationship between online game addiction and empathy in adolescents, which was indicated by a person correlation value of 0.462. This means that there is a significant relationship between online game addiction and empathy in adolescents with a moderate degree of correlation. AbstrakFenomena bermain game online di kalangan remaja merupakan suatu hal yang harus di perhatikan. Kecanduan game online membuat individu menjadi tidak peduli dengan interaksi bersama orang disekitar. Sebab individu yang telah kecanduan game online hanya terfokus pada game online. Akibatnya perasaan empati individu tersebut tidak terbentuk. Metode penelitian kuantitatif korelasi dengan skala adiksi game online dan skala empati memuat pernyataan yang bersifat favourable dan unfavourable. Sampel dalam penelitian ini 73 remaja Dusun Kalisari. Hasil penelitian terdapat hubungan yang sedang antara adiksi game online dengan empati pada remaja yang ditunjukkan dengan nilai person correlation sebesar 0,462. Artinya terdapat hubungan yang signifikan antara adiksi game online dengan empati pada remaja dengan derajat hubungan berkorelasi sedang.